2018
DOI: 10.1111/andr.12527
|View full text |Cite
|
Sign up to set email alerts
|

Sperm cryopreservation of transgender individuals: trends and findings in the past decade

Abstract: This is the largest report to date on the incidence of transgender sperm cryopreservation and comparison of semen characteristics with cisgender sperm bankers. The data reveal an increased incidence of transgender sperm banking as well as poorer semen parameters of transgender individuals compared with cisgender controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 22 publications
5
23
0
2
Order By: Relevance
“…Our findings are in line with previous studies on semen quality in trans women, which also showed a high incidence of azoospermia, oligozoospermia and asthenozoospermia ( Hamada et al , 2015 ; Li et al , 2018 ; Marsh et al , 2019 ). Only one of these studies collected data on personal behavior, feelings of depression, anxiety and stress, as well as serum hormone concentrations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in line with previous studies on semen quality in trans women, which also showed a high incidence of azoospermia, oligozoospermia and asthenozoospermia ( Hamada et al , 2015 ; Li et al , 2018 ; Marsh et al , 2019 ). Only one of these studies collected data on personal behavior, feelings of depression, anxiety and stress, as well as serum hormone concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…Although data on semen characteristics in trans women show a high incidence of impaired semen quality, these studies report on a relatively low number of people ( Hamada et al , 2015 ; Li et al , 2018 ; Marsh et al , 2019 ). The etiology could not be identified in these studies due to the small sample size and a lack of endocrine laboratory results and complete clinical data on certain lifestyle factors known to influence semen quality, such as age, obesity and cigarette smoking ( Sermondade et al , 2013 ; Johnson et al , 2015 ; Sharma et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (10) performed a retrospective review of 78 transgender sperm bankers and compared them with 141 cisgender sperm bankers from the same private cryobank. Transgender specimens showed lower sperm concentration, total motile sperm count and post-thaw sperm parameters, as well as higher incidence of oligozoospermia.…”
Section: Semen Cryopreservationmentioning
confidence: 99%
“…In the last decade, the incidence of transgender women seeking sperm cryopreservation has increased compared with cisgender men (10). In a survey of 121 transgender women performed by De Sutter et al (11), 77% reported that they would very interested in sperm banking if it was offered, and agreed that fertility preservation should be discussed with their healthcare provider.…”
Section: Introductionmentioning
confidence: 99%
“…The largest study evaluating the incidence of sperm banking and semen quality among transwomen revealed an increasing incidence of sperm cryopreservation in this population (48). Surprisingly, compared to cisgender sperm bankers, the 78 transwomen included in the study had worse semen parameters, including sperm concentration and total motile sperm count (48). Similarly, another study showed high rates of oligozoospermia, asthenozoospermia, and teratozoospermia, though there was no control group (49).…”
Section: Cryopreservation Of Sperm or Embryosmentioning
confidence: 93%